1989
DOI: 10.1128/mcb.9.11.4986
|View full text |Cite
|
Sign up to set email alerts
|

Unusual enhancer function in yeast rRNA transcription.

Abstract: The rRNA genes in most eucaryotic organisms are present in a tandem array. There is substantial evidence that transcription of one of these genes may not be independent of transcription of others. In particular, in the yeast Saccharomyces cerevisiae, the enhancer of rRNA transcription that lies 2.2 kilobases 5' of the transcription initiation site is at least partly within the upstream transcription unit. The transcription by RNA polymerase II of a wide variety of genes is profoundly influenced by cis-acting s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
2

Year Published

1990
1990
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 46 publications
3
46
2
Order By: Relevance
“…These features are orientation independence, action from either upstream or downstream of the reporter gene, and action over long distances (more than 2 kb from the promoter), which are quite different from known yeast enhancers for Pol II. In addition, using the Pol I reporter integrated at the URA3 locus, it was observed that transcription of the reporter gene increases roughly in proportion to the number of enhancer elements (10). These observations are highly consistent with the model proposed here that the enhancer element increases the probability of localization of the reporter gene to be near the nucleolus, perhaps through its interaction with rDNA, rather than by stimulating Pol I transcription directly.…”
Section: Vol 21 2001supporting
confidence: 86%
See 2 more Smart Citations
“…These features are orientation independence, action from either upstream or downstream of the reporter gene, and action over long distances (more than 2 kb from the promoter), which are quite different from known yeast enhancers for Pol II. In addition, using the Pol I reporter integrated at the URA3 locus, it was observed that transcription of the reporter gene increases roughly in proportion to the number of enhancer elements (10). These observations are highly consistent with the model proposed here that the enhancer element increases the probability of localization of the reporter gene to be near the nucleolus, perhaps through its interaction with rDNA, rather than by stimulating Pol I transcription directly.…”
Section: Vol 21 2001supporting
confidence: 86%
“…Northern analysis of RNA and Southern analysis of DNA were done by standard procedures (27). T7 reporter transcripts from plasmids YCprR8 (rR8) and YCprR10 (rR10) were detected with a 32 P-labeled antisense riboprobe prepared with pSP-T7(ϩ) by the method of Johnson and Warner (10). Analysis of the 5Ј end of 35S rRNA by primer extension was performed by using a 32 P-labeled primer which hybridizes to the 35S rRNA external transcribed spacer as described previously (36).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our ChIP data localized Rat1 to both IGS1 and the 5Ј region of the 35S rDNA, possibly reflecting looping of the rDNA as proposed previously (Johnson and Warner 1989;Kulkens et al 1992). This might arise through oligomerization of Reb1, since this binds the rDNA at T1 in IGS1 and just upstream of the Pol I promoter in IGS2 (Reeder and Lang 1997).…”
Section: S Cerevisiae the Model Illustrated Insupporting
confidence: 84%
“…Its effect is relatively independent of position and orientation (10). Unlike enhancers of RNA polymerase II in S. cerevisiae, this enhancer is active even when downstream of its target gene (15).…”
mentioning
confidence: 99%